2020
DOI: 10.3389/fcell.2020.00501
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epithelial-Mesenchymal Transition in Retinal Pigment Epithelium Dysfunction

Abstract: Retinal pigment epithelial (RPE) cells maintain the health and functional integrity of both photoreceptors and the choroidal vasculature. Loss of RPE differentiation has long been known to play a critical role in numerous retinal diseases, including inherited rodcone degenerations, inherited macular degeneration, age-related macular degeneration, and proliferative vitreoretinopathy. Recent studies in post-mortem eyes have found upregulation of critical epithelial-mesenchymal transition (EMT) drivers such as TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 124 publications
2
101
0
Order By: Relevance
“…Therapeutic interventions against RPE EMT have largely been explored in mechanistic experiments using in vitro cell culture and in vivo animal models. To date, some promising drug candidates have been trialed in preclinical studies of PVR, including TGF-β receptor inhibitors, peroxisome proliferator-activated receptor (PPAR)-γ agonists, retinoic acid receptor-γ (RAR-γ) agonists and methotrexate ( Shu, Butcher & Saint-Geniez, 2020 ; Zhou et al, 2020 ). Nassar et al (2014) found that TGF-β receptor 1 inhibitor LY-364947 (LY) attenuates RPE cell transdifferentiation in vitro, and that intravitreal injection of LY completely prevents PVR and TRD in vivo.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Therapeutic interventions against RPE EMT have largely been explored in mechanistic experiments using in vitro cell culture and in vivo animal models. To date, some promising drug candidates have been trialed in preclinical studies of PVR, including TGF-β receptor inhibitors, peroxisome proliferator-activated receptor (PPAR)-γ agonists, retinoic acid receptor-γ (RAR-γ) agonists and methotrexate ( Shu, Butcher & Saint-Geniez, 2020 ; Zhou et al, 2020 ). Nassar et al (2014) found that TGF-β receptor 1 inhibitor LY-364947 (LY) attenuates RPE cell transdifferentiation in vitro, and that intravitreal injection of LY completely prevents PVR and TRD in vivo.…”
Section: Survey Methodologymentioning
confidence: 99%
“…The epigenetic transcriptome analyses of human AMD-RPE unveiled an association between RPE senescence and the epigenetic dysregulation, such as a differentiation of methylated SKI proto-oncogene, which is a negative regulator of the TGF-β pathway [ 56 ]. As a consequence, the over-activated TGF-β signaling induces a SIPS in RPE cells [ 69 ] and facilitates an epithelial-mesenchymal transition (EMT), leading to loss of RPE differentiation and compromised cellular function [ 70 ]. We have recently demonstrated that RPE cells deficient in interleukin-1 receptor-associated kinase-M (IRAK-M), a key inhibitor of TLR/IL-1R-mediated inflammation, are more susceptible to oxidative stress-induced senescence, evidenced by elevated SA-β-Gal and p21 CIP1 expression, increased secretion of SASP proteins HMGB1 and IL-6, and decreased nuclear lamina protein LB1.…”
Section: Senescence Occurs In a Variety Of Retinal Cellsmentioning
confidence: 99%
“…ETM consists in the loss of epithelial cell polarity and cell-cell adhesion and the acquisition of migratory and invasive properties as mesenchymal stem cells. This process RPE-ETM has been found to be linked to TGF-β upregulation, UPR mt dysfunctions, yet, as reported by Zhou et al and Hyttinen et al, NAM treatment prevented ETM in numerous RPE cell models, orchestrating the mechanism responsible for that shift [ 211 , 212 ].…”
Section: Supplementing Nad + As a Therapeutic Amentioning
confidence: 99%